2020
DOI: 10.3389/fcimb.2020.00200
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Virulence Profiles of Enteroaggregative Escherichia coli (EAEC) Isolated From Deployed Military Personnel (DMP) With Travelers' Diarrhea

Abstract: To discern if there was a particular genotype associated with clinical enteroaggregative Escherichia coli (EAEC) strains isolated from deployed military personnel (DMP) with travelers' diarrhea (TD), we characterized a collection of EAEC from DMP deployed to Afghanistan, Djibouti, Kenya, or Honduras. Although we did not identify a specific EAEC genotype associated with TD in DMP, we found that EAEC isolated at the first clinic visit were more likely to encode the dispersin gene aap than EAEC collected at follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 73 publications
3
36
2
Order By: Relevance
“…The lack of aggR gene in half of our EAEC isolates coincide with Lima´s findings, and the authors suggested that this gene is not a useful virulence marker for diagnosis in opposite to what was suggested by other studies and that this gene alone is not a sensitive target and much less specific than the aatA gene (2,18). In recent years case-control and epidemiological studies have used several EAEC virulence genes, and aatA, aap, aagR, astA, and aafA were among the most frequently used for EAEC diagnosis (12,20,69). Also, Jenkins, Chart (49) suggested that aaiA, a chromosomal -encoded gene, would improve EAEC diagnosis.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The lack of aggR gene in half of our EAEC isolates coincide with Lima´s findings, and the authors suggested that this gene is not a useful virulence marker for diagnosis in opposite to what was suggested by other studies and that this gene alone is not a sensitive target and much less specific than the aatA gene (2,18). In recent years case-control and epidemiological studies have used several EAEC virulence genes, and aatA, aap, aagR, astA, and aafA were among the most frequently used for EAEC diagnosis (12,20,69). Also, Jenkins, Chart (49) suggested that aaiA, a chromosomal -encoded gene, would improve EAEC diagnosis.…”
Section: Discussionsupporting
confidence: 58%
“…The aap genes that encode for dispersin was the most prevalent virulence gene among all EAEC isolates; similarly to us, other studies found aap in high proportions (19,31,67). Despite the fact that dispersin was also found among other diarrheagenic E.coli pathotypes and nonpathogenic E.coli (68), several studies focused on EAEC isolates have shown that aap gene was highly prevalent virulent marker and associated with diarrheal cases (56)(57)(58)69). Since the aap gene showed to be a nonexclusive EAEC virulence gene, its addition to the initial detection for EAEC will not improve the identification of EAEC isolates.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Further, regarding microbial biofilm, nearly 80% of microbial infections in the living system involve biofilm formation (Batoni et al, 2016). Biofilm constitutes a syntrophic association of microbes enclosed within extracellular polymeric substance matrix that prevents microorganisms from adverse external influences, particularly antimicrobial agents (Lin et al, 2017;Petro et al, 2020). The adhesion of MDR-EAEC strains by MATS in this study was found to be comparatively higher to the tested monopolar solvent, chloroform, than to the apolar solvent, n-hexadecane, which bears almost identical van der Waal's properties.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, EAEC is regarded as a heterogeneous pathogen; the pathogenicity of EAEC is described initially by its surface adherence to the intestinal mucosa, followed by biofilm formation and toxin release, which often ends up with an inflammatory response (Lima et al, 2018). The biofilm formation by EAEC is correlated well with the persistence of infection and recalcitrance to empirical antimicrobial treatment (Lin et al, 2017;Petro et al, 2020). This persistent colonization of EAEC leads to carrier status, enabling antibiotic pressure, which results in frightening levels of multi-drug resistance.…”
Section: Introductionmentioning
confidence: 99%